2018
DOI: 10.1002/jcp.27235
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback loop of lncRNA LINC01296/miR‐598/Twist1 promotes non‐small cell lung cancer tumorigenesis

Abstract: Emerging evidence has illustrated the vital roles of long noncoding RNAs (lncRNAs) in human cancers. However, the role of lncRNAs in non-small cell lung cancer (NSCLC) is still elusive and poorly understood. In the current study, our team conducted extensive experiments to identify the role of long intergenic nonprotein coding (LINC01296) on NSCLC tumorigenesis. The results illustrated that the elevated LINC01296 expression in NSCLC tissue specimens and cell lines were closely correlated with the poor prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…35 A similar positive feedback loop was found in the LINC01296/miR-598/Twist1 axis in NSCLC. 36 These findings indicate that FBXW7 or an FBXW7-related molecule may mediate the transcription of hsa_circ_11780 by functioning as a transcription factor in NSCLC. Nonetheless, this requires further exploration in future studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…35 A similar positive feedback loop was found in the LINC01296/miR-598/Twist1 axis in NSCLC. 36 These findings indicate that FBXW7 or an FBXW7-related molecule may mediate the transcription of hsa_circ_11780 by functioning as a transcription factor in NSCLC. Nonetheless, this requires further exploration in future studies.…”
Section: Discussionmentioning
confidence: 81%
“…An increasing number of reports state that interfering with the transcription of ncRNAs, by binding to their promotor regions, is the main feedback pattern of the downstream functional protein. [34][35][36] Zinc finger E-box binding homeobox 1 (ZEB1), which is downstream of the long noncoding RNA (lncRNA) ZEB1 antisense RNA 1(ZEB1-AS)/miR-409-3p, can activate the lncRNA ZEB1-AS expression by binding to its promoter region. 34 lncRNA CASC11 transcription was accelerated when the transcription factor FOXO3 translocated to the promoter of CASC11.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01296 has been reported to be dysregulated in different types of cancers. Moreover, LINC01296 was found to play an important role in multiple cellular processes involved in malignant tumour, such as cell proliferation, invasion and migration, by targeting messenger RNA,26 regulating microRNA27 or competing with the endogenous RNA 18. A study from Yuan et al demonstrated that overexpression of LINC01296 was associated with advanced tumour stages and positive lymph node metastasis in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Long intergenic non-coding RNA 01296 (LINC01296) is a novel intergenic lncRNA located at chromosome 14q11.2 18. Abnormal expression of LINC01296 has been found in various malignant tumours, including colorectal cancer,19 bladder cancer,20 prostate cancer,21 gastric cancer,22 cholangiocarcinoma,23 breast cancer,24 pancreatic cancer,25 osteosarcoma,26 lung cancer27 and oesophageal carcinoma 28. Some studies showed that overexpression of LINC01296 was associated with the clinicopathological features and poor prognosis in different cancers 21 24.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNA CRNDE shows a high level in tongue squamous cell carcinoma tissues and inhibits miR-384 to facilitate cell proliferation and metastasis [11]. Besides, highlyexpressed LINC01296 is revealed to predict poor prognosis in lung cancer patients and enhances tumor growth via modulating miR-598/Twist1 pathway [12]. Importantly, mounting reports indicated that lncRNAs regulate gene expression to mediate cancer progression through multiple ways, such as histone modi cation, transcriptional and post-transcriptional regulation [13].…”
Section: Introductionmentioning
confidence: 99%